Pineapple Bark Performance in Dyes Adsorption: Optimization by the Central Composite Design - Ahlam Fegousse; Abdelali El Gaidoumi; Youssef Miyah; Rabea El Mountassir; Anissa Lahrichi (Journal of Chemistry)
This work is concerned with the study of the adsorption in aqueous medium of a three-dye mixture which contains Methylene Blue, Brilliant Green, and Congo Red on the pineapple bark. This adsorbent material has been characterized by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). The experimental design methodology, based on the response surface methodology (RSM) by the central composite design (CCD), has been applied for the optimization of the parameters, namely, the temperature, dose of the adsorbent, and pH. The yield reached 98.91% under optimal conditions (T = 30°C; adsorbent dose = 2.5 g·L−1; pH = 9.8) at an initial concentration of 20 mg·L−1.